Politik Uang dalam Pilkada 2024 Kabupaten Jayapura: Antara Legitimasi Sosial dan Perilaku Memilih - Yasin, Hendra; Kadji, Jurisman (Prodi Tata Negara (Siyasah) IAIN Langsa, 2024)
This study examines the prevalence of money politics in the 2024 Regional Head Election (Pilkada) in Jayapura Regency, considering its impact on social legitimacy and the electoral behavior of local communities. The research aims to analyze public acceptance and preferences regarding different forms of money politics and the extent to which it influences voting decisions. Three key factors are observed: acceptance, its influence on voting behavior, and the most preferred form of monetary incentives. This study employs a quantitative methodology using a survey. Data collection was conducted through stratified multistage random sampling, involving 440 respondents. The findings reveal several important insights. First, the acceptance of money politics is notably high. Second, financial assistance is the most preferred form of incentive. Lastly, monetary incentives do not operate independently in shaping electoral choices; rather, they function within a broader patron-client framework.